Development of Entrepreneurship Intentions among School Students in Malaysia - Afiah Sheikh Ismail; Nor Aishah Buang (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2019)
Entrepreneurial education in school has long been an effort by authorities in improving participation among school leavers in entrepreneurship. Still, there are clear obstacle in making this a reality. Thus this conceptual paper will discuss the obstacles and solutions towards of making entrepreneurial education a success. Obstacles that will be discussed are such as the lack of knowledge of entrepreneurship among teachers and the obsolete methods of teaching and learning currently practiced. Several solutions to the obstacles will be addressed are such as new pedagogical approaches such as games and simulations. Plus, solutions from the industry itself is put forward with activities such as engagement and attachment being highlighted. Therefore a model framework has been develop form the combination of elements from past theories and models which are Critical Experiential Incidence Model by Krueger(2007), Constructivism Theory by Vygotsky (1978) and Theory of Planned Behavior by Ajzen (1991).